New Economics of Venture Capitalism? Assessing the Role of Remittances on Household Entrepreneurship - Chakaniza, Peter (Graduate School of Business (GSB), 2024)
Remittance flows have often been considered a significant source of flow of foreign capital flows into African countries but are not often considered a key source of potential investment income for entrepreneurial activities and often have higher cost corridors in Southern Africa compared to other regions. This paper seeks to analyse the effects of remittance receipt on the likelihood to engage in household entrepreneurship in Malawi using cross sectional data from the Fifth Malawi Integrated Household Survey 2019-2020 covering 11,434 households. Analysis is made using a bivariate Probit estimation technique on overall households, as well as female-headed households, who often make up the majority of microenterprise owners and need capital to survive. By using household data, this study takes into account the behaviour of both formal and informal enterprises in a way that has not been assessed by previous studies. The study finds that when looking at overall households, the effects of remittances on household entrepreneurship is positive and significant, however the results lose significance when internet access as a control variable is utilised. For female headed households, remittance receipt is associated with a lower likelihood of engaging in entrepreneurial activities. This may suggest a deeper need to support female entrepreneurs with additional capital, to help their businesses thrive. There is a need to develop a better overarching conditions and capacity to help foster overall entrepreneurial pursuits.